Racial, Social, and Clinical Determinants of Hepatocellular Carcinoma Surveillance - Singal, Amit G. (Am J Med, 2014)
BACKGROUND: Fewer than 1 in 5 patients receive hepatocellular carcinoma surveillance; however, most studies were performed in racially and socioeconomically homogenous populations and few used guideline-based definitions for surveillance. AIMS: To characterize guideline-consistent hepatocellular carcinoma surveillance rates and identify determinants of hepatocellular carcinoma surveillance among a racially and socioeconomically diverse cohort of cirrhotic patients. METHODS: We retrospectively characterized hepatocellular carcinoma surveillance among cirrhotic patients followed between July 2008 and July 2011 at an urban safety-net hospital. Inconsistent surveillance was defined as at least one screening ultrasound during the 3-year period, annual surveillance as screening ultrasounds every 12 months, and biannual surveillance as screening ultrasounds every 6 months. Univariate and multivariate analyses were conducted to identify predictors of surveillance. RESULTS: Of 904 cirrhotic patients, 603 (67%) underwent inconsistent surveillance. Failure to recognize cirrhosis was a significant barrier to surveillance utilization (p<0.001). Inconsistent surveillance was associated with insurance status (OR 1.43, 95%CI 1.03–1.98), multiple primary care visits per year (OR 2.63, 95%CI 1.86–3.71), multiple hepatology visits per year (OR 3.75, 95%CI 2.64–5.33), African American race (OR 0.61, 95%CI 0.42–0.99), nonalcoholic steatohepatitis etiology (OR 0.60, 95%CI 0.37–0.98), and extrahepatic cancer (OR 0.43, 95%CI 0.24–0.77). Only 98 (13.4%) of 730 patients underwent annual surveillance, and only 13 (1.7%) of 786 had biannual surveillance. CONCLUSIONS: Only 13% of patients with cirrhosis receive annual surveillance and less than 2% receive biannual surveillance. There are racial and socioeconomic disparities, with lower rates of hepatocellular carcinoma surveillance among African Americans and underinsured patients.